2017
DOI: 10.1155/2017/5740851
|View full text |Cite
|
Sign up to set email alerts
|

Growth Profile and Its Association with Nutrient Intake and Dietary Patterns among Children and Adolescents in Hail Region of Saudi Arabia

Abstract: Hail region of Saudi Arabia (KSA) has the highest adult obesity rates in the entire kingdom and limited information is available about the prevalence and patterns of growth markers. Therefore, it is important to monitor the growth trends to implement effective public health preventive strategies for the region. This study aims to estimate the prevalence of growth profile patterns (stunting, wasting, underweight, and overweight) and its associations with nutrient intake and dietary patterns among children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 22 publications
2
32
1
2
Order By: Relevance
“…On statistical analysis of distribution of Z-score in both groups was insignificant as DC group had 55% normal growth whereas HR group had 40% normal growth and very few comes under obese (35% and 50%) and underweight (10% and 10%) in both groups respectively (Table 2). Alshammariet al (2017) conducted a study on growth profile using z-scores and observed a contrast results from present study, the prevalence of 4.73% moderate and 1.54% severe underweight; 6.65% moderate and 2.59% severe stunting; 6.34% moderate and 2.55% severe wasting was present in the study population 4 . …”
Section: Results and Discussion:-contrasting
confidence: 63%
See 1 more Smart Citation
“…On statistical analysis of distribution of Z-score in both groups was insignificant as DC group had 55% normal growth whereas HR group had 40% normal growth and very few comes under obese (35% and 50%) and underweight (10% and 10%) in both groups respectively (Table 2). Alshammariet al (2017) conducted a study on growth profile using z-scores and observed a contrast results from present study, the prevalence of 4.73% moderate and 1.54% severe underweight; 6.65% moderate and 2.59% severe stunting; 6.34% moderate and 2.55% severe wasting was present in the study population 4 . …”
Section: Results and Discussion:-contrasting
confidence: 63%
“…Total 40 subjects were recruited of the age 2-5 years. The Inclusion criteria of the study was 1) age should be 2-5 years, 2) willing to participate in the study and 3) should not be suffering with any chronic disease 4 . A pretested questionnaire was used for data collection.…”
Section: Designs and Methods:-mentioning
confidence: 99%
“…Fifty‐one studies met the inclusion criteria and were included in the literature review. All these studies were observational studies, 50 were cross‐sectional 17–66 and one was a case‐control design 67 . Seventeen were published in national journals and 34 in international journals.…”
Section: Resultsmentioning
confidence: 99%
“…However, significant interstudy heterogeneity was noted (I 2 = 72%) owing to differences in evaluation parameters. On the other hand, the association between father education and the prevalence of overweight and obesity in Saudi adolescents was reported in six studies 25,26,37,47,58,60,61 that indicated a statistically significant ( P = .0005) positive association between fathers with the highest level of education and odds of overweight and obesity (Table 3, Figure 5F). Low interstudy heterogeneity was noted (I 2 = 10%).…”
Section: Discussionmentioning
confidence: 98%
“…59,61,63,64,66,67 Dietary patterns may also vary depending on the cultural and economic context, 52 as well as other factors, such as lifestyle and level of physical activity. Alshammari et al 44 highlighted that, currently, living standards are on the rise, leading to complex changes in diet, lifestyle, and health.…”
Section: Discussionmentioning
confidence: 99%